Secukinumab Treatment in Patients with Spondyloarthritis and Concomitant Demyelinating Disease: Rationale of IL-17 Inhibition and Clinical Outcome - Scrivo, Rossana; Diamanti, Andrea Picchianti; Chimenti, Maria Sole; Molteni, Emanuele; Sciarra, Giorgio; Bari, Federico; Greco, Elisabetta; Bergamini, Alberto; Laganà, Bruno; Conti, Fabrizio (Archives of Clinical and Medical Case Reports, 2022)
For patients with spondyloarthritis (SpA), the coexistence of demyelinating diseases complicates the choice of the therapeutic agent, as demyelinating diseases should not be targeted with tumor necrosis factor inhibitors. However, targeting interleukin (IL)-17 may have a beneficial effect on both diseases. Secukinumab is a monoclonal antibody that selectively binds to and inhibits IL-17A. To date, there have been only a handful of case studies reporting the use of secukinumab in patients with concomitant SpA and multiple sclerosis (MS), showing good efficacy and safety profiles. Here, we focus on the rationale of inhibiting IL-17 with secukinumab in the setting of concomitant SpA and demyelinating diseases, also discussing the clinical outcome experienced in patients. Currently, secukinumab seems the only safe treatment for patients with concomitant SpA and MS.